Hurwitz Zeta Function Is Prime - Marius Dundulis; Ramūnas Garunkštis; Erikas Karikovas; Raivydas Šimėnas (Mathematics, 2023)
We proved that the Hurwitz zeta function is prime. In addition, we derived the Nevanlinna characteristic for this function.